Crosstalk between hepatitis B virus X and high‐mobility group box 1 facilitates autophagy in hepatocytes. Issue 3 (24th January 2018) - Fu, Sha; Wang, Juan; Hu, Xingwang; Zhou, Rong‐rong; Fu, Yongming; Tang, Daolin; Kang, Rui; Huang, Yan; Sun, Lunquan; Li, Ning; Fan, Xue‐Gong
Abstract : Hepatitis B virus (HBV) X (HBx) protein is a pivotal regulator of HBV‐triggered autophagy. However, the role of HBx‐induced epigenetic changes in autophagy remains largely unknown. The cytoplasmic (Cyt) high‐mobility group box 1 (HMGB1) has been identified as a positive regulator of autophagy, and its Cyt translocation is closely associated with its acetylation status. Here, we evaluated the function of HMGB1 in HBx‐mediated autophagy and its association with histone deacetylase (HDAC). Using cell lines with enforced expression of HBx, we demonstrated that HBx upregulated the expression of HMGB1 and promoted its Cyt translocation by acetylation to facilitate autophagy. We further identified the underlying mechanism by which decreased nuclear HDAC activity and expression levels contribute to the HBx‐promoted hyperacetylation and subsequent translocation of HMGB1. We also identified the HDAC1 isoform as a critical factor in regulating this phenomenon. In addition, HBx bound to HMGB1 in the cytoplasm, which triggered autophagy in hepatocytes. Pharmacological inhibition of HMGB1 Cyt translocation with ethyl pyruvate prevented HBx‐induced autophagy. These results demonstrate a novel function of acetylated HMGB1 in HBx‐mediated autophagy in hepatocytes. Abstract : Here, we show that hepatitis B virus X (HBx) contributes to high‐mobility group box 1 (HMGB1) cytoplasmic translocation via histone deacetylase (HDAC) inhibition in the setting of hepatitis B virus (HBV) infection. HDACs tilt the acetylation/deacetylation balance of HMGB1 in response to HBx. HBx contributes to the interaction between HMGB1 and Beclin1 to induce autophagy, which participates in the pathological process of HBV replication and hepatocellular carcinoma development.